The relative importance of multiple invasion mechanisms - Yu-Fei Zhao; Shu-Qi Zhou; Zuo-Fu Wei; Bao-Shan Zhao; Li-Jia Dong (Global Journal of Ecology - Peertechz Publications, 2020)
Aim: Plant invasions are driven by suites of factors in nature. To better understand the success of invasive plants, it is crucial to quantify the relative importance of multiple invasion mechanisms during plant invasions. Location: Eastern China. Methods: We surveyed 300 pairs of uninvaded and invaded quadrats by Solidago canadensis across its entire invaded range, quantified its invasion intensities, and identified the relative importance of 19 causal factors and 11 invasion hypotheses using the multimodel inference approach. Results: The relative contributions of all the 19 factors to S. canadensis invasion varied depending on different invasion intensities, so did the relative importance of 11 different hypotheses vary with invasion intensities. At the low invasion intensity, abiotic factors dominated over biotic factors; in contrast, biotic factors dominated over abiotic factors at the high invasion intensity. The role of S. canadensis-recipient community interactions was highly important. Main conclusions: These findings suggest that the relative importance of multiple invasion mechanisms may be staged in a real invasion. Based on our results, we propose a novel nature-sieve hypothesis, which provides a universal framework for an understanding of successful invasion.